CONSUMER PERCEPTION ABOUT GEOGRAPHICAL INDICATION CERTIFIED PRODUCTS: AN EMPIRICAL STUDY - Dr. Ashish Puranik 1, Dr. Asama Bagwan 2, Dr. Rahuk Kulkarni 3 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Geographical Indication is a certification for genuinity of products. The concept of GI will gain impact in the market if consumers understand the GI tag and identify GI tagged products. Researchers thought upon the analysis of consumers perceptions on GI. The present study focuses on studying consumer perception about GI-tagged products. Primary Data from 197 respondents is collected. The study reveals purchase intention, purchase frequency, purchase determinants, and purchase occasion of GI-tagged products and some qualitative responses about enhancing the economic impact of GI-tagged products. One-way ANOVA and F test to test the hypotheses. It is suggested that the government should launch an advertisement campaign to promote GI-tagged products since consumers prefer to purchase such products as tourist. Further recommended that direct marketing would be the most effective strategy for making available authentic GI-tagged products. Recently there has been use of blockchain technology chips in Kolhapuri chappals (GI-tagged leather footwear in Maharashtra) and special packaging material for Devgad Alphonso Mangoes to prevent the sale of counterfeit products. This study recommends tools to enhance the economic impact of GI products.